2013
DOI: 10.2134/agronj2013.0015
|View full text |Cite
|
Sign up to set email alerts
|

Allometric Models for Estimating Carbon Fixation in Citrus Trees

Abstract: Citrus fruits play an important part in the Spanish agricultural sector. These orchards could play an important role as a terrestrial C sink and contribute to C fixation. We proposed quantifying the net primary production in different‐aged citrus trees through the measurement of annual increases in the C content of the biomass of trees of different ages completely excavated. The measured net primary production in mature citrus was 27 kg C tree–1 (1143 g C m–2 yr–1; 11.4 Mg C ha–1 yr–1) with a similar behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
(98 reference statements)
0
5
1
Order By: Relevance
“…The tree biomass measured in our study at age 7 years was only reached at age 11 years in Spain, where trees are considered adult from age 8 years onwards. The rates of biomass accumulation were slower in the Spanish orchards sampled by Quiñones et al (2013) than in our study and only 27% of the total biomass was found belowground in 8-year-old trees (\20% from age 10 years onwards), while root biomass accounted for 35-38% of the total biomass in our Brazilian orchard.…”
Section: Biomass Production and Consequences For The Management Of Orcontrasting
confidence: 73%
See 1 more Smart Citation
“…The tree biomass measured in our study at age 7 years was only reached at age 11 years in Spain, where trees are considered adult from age 8 years onwards. The rates of biomass accumulation were slower in the Spanish orchards sampled by Quiñones et al (2013) than in our study and only 27% of the total biomass was found belowground in 8-year-old trees (\20% from age 10 years onwards), while root biomass accounted for 35-38% of the total biomass in our Brazilian orchard.…”
Section: Biomass Production and Consequences For The Management Of Orcontrasting
confidence: 73%
“…(Raf. ), which represents [70% of the orange production in Spain (Quiñones et al 2013). The tree biomass measured in our study at age 7 years was only reached at age 11 years in Spain, where trees are considered adult from age 8 years onwards.…”
Section: Biomass Production and Consequences For The Management Of Ormentioning
confidence: 90%
“…Citrus The citrus biomass dataset only comprises data from literature, from two references in particular. Quiñones et al (2013) showed aboveground and belowground biomass data from 2-to 14-year-old Navelina orange trees (Citrus sinensis L.) in Valencia (Eastern Spain), while Iglesias et al (2013) showed aboveground and belowground biomass data from 2to 14-year-old Clemenules trees (Citrus clementina Hort. ex Tan.)…”
Section: Estimation Of Above-and Belowground Biomassmentioning
confidence: 99%
“…In this respect, promoting carbon sequestration and storage in biomass and soils has become one of the most important mitigation measures in the fight against climate change. Therefore, reliable evaluation of C fixation in terrestrial sinks would be useful, in order to quantify their spatial and temporal variability, gain a better understanding of the carbon cycle and assist mitigation policies worldwide (Quiñones et al 2013;Huffman et al 2015). Moreover, although plants are able to capture atmospheric CO 2 , their effectiveness as a C sink depends on residence times (Quiñones et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation